The Retention Phase of Treatment Retention - Still the Stepchild - Roberts Graeme (Sciendo, 1993)
This is the second in a series of three articles on The Retention Phase of Treatment taken from presentations given at the 1992 Annual Clinical Day meeting of the Victorian Branch of the A.S.O.